2010
DOI: 10.1299/jamdsm.4.838
|View full text |Cite
|
Sign up to set email alerts
|

Temperature History and Metallographic Structure of 0.45%C Steel Processed by Frictional Stir Burnishing

Abstract: Significant enhancement of hardness characteristics was achieved through the Frictional Stir Burnishing (FSB) process. The enhanced region was generated by the FSB process where the thickness and hardness were approximately 200 µm and 900 HV, respectively, under the conditions of spindle speed of 10000 min -1 , a feed rate of 200 mm/min and a processing load of 750 N. The processing temperature was approximately 600~750 ˚C under compressive stress condition. Although this temperature is lower than A 3 transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
3
0
2
Order By: Relevance
“…機械部品には高機能化,長寿命化が求められる.特に動力伝達部材として多用されるシャフト材は,高硬度化 による耐摩耗性向上や圧縮残留応力付与による疲労強度の向上が要求される.その要求に対して,高周波焼入れ (Kristoffersen and Vomacka, 2001)やショットピーニング (Fujii, et al, 2009).摩擦攪拌プロセスは加工面に熱と強ひずみを付与することで,金属表面の結晶粒の微細 化や高硬度化が可能である.しかし,これらの表面強化技術の多くは形状加工後の追加工程であり,別装置を用 いることとなるため段取り替えが必要となる.切削形の工作機械で形状加工後に直ちに必要部分の表面強化まで 行うことができれば,設備投資や段取り替えなどが減り,時間とコストを削減できる. このような課題に対して,笹原ら (Sasahara, et al, 2008 ;笹原他, 2009 ;Kiuchi and Sasahara, 2010 応力が大きくなることが報告されている …”
Section: 緒 言unclassified
“…機械部品には高機能化,長寿命化が求められる.特に動力伝達部材として多用されるシャフト材は,高硬度化 による耐摩耗性向上や圧縮残留応力付与による疲労強度の向上が要求される.その要求に対して,高周波焼入れ (Kristoffersen and Vomacka, 2001)やショットピーニング (Fujii, et al, 2009).摩擦攪拌プロセスは加工面に熱と強ひずみを付与することで,金属表面の結晶粒の微細 化や高硬度化が可能である.しかし,これらの表面強化技術の多くは形状加工後の追加工程であり,別装置を用 いることとなるため段取り替えが必要となる.切削形の工作機械で形状加工後に直ちに必要部分の表面強化まで 行うことができれば,設備投資や段取り替えなどが減り,時間とコストを削減できる. このような課題に対して,笹原ら (Sasahara, et al, 2008 ;笹原他, 2009 ;Kiuchi and Sasahara, 2010 応力が大きくなることが報告されている …”
Section: 緒 言unclassified
“…One of the author of this paper proposed friction stir burnishing (FSB) [19][20][21] as one of the frictional stir process. Figure 1 contains a schematic of the FSB process.…”
Section: Introductionmentioning
confidence: 99%
“…An experiment has been performed in [3] with a tool rotation frequency of 10,000 rpm, a feed of 200 mm/min, and load on a tool of 750 N. A temperature was achieved in the joint zone of 600 -750°C. It has been demonstrated that after this treatment there is an increase in surface layer hardness.…”
Section: Introductionmentioning
confidence: 99%